The relationship between spousal support and anxiety levels in mothers undergoing pre-cesarean section - Annisa Rizka Aryani; Sarwinanti Sarwinanti; Warsiti Warsiti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Cesarean section is an operative delivery procedure that often causes psychological responses in mothers, one of which is anxiety. Preoperative anxiety can affect the mother's physiological condition and the recovery process after the procedure. One psychosocial factor that can influence anxiety is spousal support, as the husband is the main source of emotional support for the mother during childbirth. Purpose: To determine the relationship between spousal support and the level of anxiety in mothers undergoing pre-cesarean section. Method: This study used a correlational quantitative design with a cross-sectional approach. The study was conducted from January 3 to January 23, 2026, at Nyi Ageng Serang Regional General Hospital and Queen Latifa General Hospital. The sampling technique used was Accidental Sampling. Spousal support was measured using a support questionnaire, while anxiety levels were measured using the HARS scale. Data analysis was performed using the Spearman Rank test. Results: The results of the analysis showed a relationship between husband support and the anxiety levels of mothers undergoing pre-sectio caesarean delivery with a correlation coefficient of 0.454, indicating a moderate relationship, and a significance value of p = 0.034 (<0.05). Conclusion: There is a relationship between spousal support and anxiety levels in mothers undergoing pre-cesarean section delivery. The better the spousal support provided, the lower the mother's anxiety in facing cesarean section delivery.